A practical workflow for fixation and autofluorescence reduction in correlative light and electron microscopy of postmortem human brain tissue - Lee, Ha-Eon; Kim, Hong Lim; Cho, Ara; Kim, Do-Gyun; Park, Min-Jin; Oh, Yuna; Park, Yong Soo; Han, Rafael T.; Lee, Mun-yong; Riew, Tae-Ryong (Churchill Livingstone, 2026)
Background Correlative Light and Electron Microscopy (CLEM) on postmortem human brain tissue is limited by poor ultrastructural preservation and high endogenous autofluorescence. Furthermore, many existing protocols lack the flexibility required for brain banking, where tissues are preserved for diverse, unplanned future studies. The aim of this study was to establish an effective, flexible preservation and processing workflow for CLEM analysis of postmortem human brain tissue. Methods We evaluated different fixation protocols (4 % paraformaldehyde [PFA] vs. 4 % PFA + 0.2 % glutaraldehyde [GLA]) and autofluorescence quenching agents on cryopreserved human medial prefrontal cortex tissue. Immunofluorescence intensity for glial and neuronal markers and ultrastructural integrity was assessed via confocal and transmission electron microscopy (TEM). Results The addition of 0.2 % GLA to 4 % PFA significantly improved the ultrastructure without compromising immunoreactivity for most markers. In contrast, autofluorescence quenchers, while reducing background signal and autofluorescence, severely degraded ultrastructure, rendering them unsuitable for subsequent electron microscopy analysis. Using this established protocol (4 % PFA + 0.2 % GLA without quenchers), we successfully performed high-fidelity CLEM, correlating immunolabeled neuronal structures to their ultrastructural counterparts and identifying perinuclear autofluorescence as lipofuscin granules. Conclusion We established an adaptive workflow for postmortem human brain tissue that balances ultrastructural preservation and antigenicity. Fixation with 4 % PFA + 0.2 % GLA followed by cryopreservation creates a flexible, high-quality tissue archive. For high-fidelity CLEM or electron microscopy analysis, solvent-based quenchers like Sudan Black B must be omitted. This protocol enhances the utility of irreplaceable human brain samples for multimodal neuropathological studies.